?VARIATION IN CHEMICAL CONSTITUENTS OF MANGROVE FOLIAGE A VICENNIA MARINA (FORSK.) VIERH. (AVICENNIACEAE) (Biological Sciences - PJSIR, 1994)
Seasonal variation in the organic and inorganic constituents of green, yellow and decomposing mangrove, Avicen- nia marina, leaves were studied. The leaf samples were collected from two different locations and analysed for total or- ganic matter, water,protein, lipid, carbohydrate, nitrogen, organic carbon, and calorific content. Total inorganic content and the macro and micro-elements including sodium, potassium, calcium, magnesium, phosphorus, iron, manganese and copper were also determined. Results showed differences among leaf types and also between the sampling sites. The heavy metal pollution in the creek area was also reflected in the leaf samples from Bakran creek.